2014
DOI: 10.1021/cb400547u
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Nitrosative Stress: Protein S-Oxidation Accompanies S-Nitrosylation

Abstract: Reversible chemical modifications of protein cysteine residues by S-nitrosylation and S-oxidation are increasingly recognized as important regulatory mechanisms for many protein classes associated with cellular signaling and stress response. Both modifications may theoretically occur under cellular nitrosative or nitroxidative stress. Therefore, a proteomic isotope-coded approach to parallel, quantitative analysis of cysteome S-nitrosylation and S-oxidation was developed. Modifications of cysteine residues of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 59 publications
1
28
1
Order By: Relevance
“…One major reason is that methodological identification of SNO is challenging and the specificity of the reaction and its mechanism(s) are poorly understood (10). The difficulty of experimentally discerning SNO from further thiol oxidation was recently illustrated by a proteomic isotopecoded approach (d-SSwitch) that could quantify concurrently both SNO and S-oxidation to disulfide for specific Cys(s) and showed that oxidation dominates over SNO upon CSNO treatment (110). On the contrary, endogenous S-nitrosated proteins have been identified in vivo using a methodology based on mercury resin enrichment or chromatography fractionation with high-resolution MS.…”
Section: Identification and Role Of Sno In Sgcmentioning
confidence: 99%
“…One major reason is that methodological identification of SNO is challenging and the specificity of the reaction and its mechanism(s) are poorly understood (10). The difficulty of experimentally discerning SNO from further thiol oxidation was recently illustrated by a proteomic isotopecoded approach (d-SSwitch) that could quantify concurrently both SNO and S-oxidation to disulfide for specific Cys(s) and showed that oxidation dominates over SNO upon CSNO treatment (110). On the contrary, endogenous S-nitrosated proteins have been identified in vivo using a methodology based on mercury resin enrichment or chromatography fractionation with high-resolution MS.…”
Section: Identification and Role Of Sno In Sgcmentioning
confidence: 99%
“…To distinguish S-nitrosylation from GSH-protein adducts in vivo is technically difficult because (i) reactive nitrogen species such as S-nitrosoglutathione (GSNO) or peroxynitrite (ONOO − ) can induce both S-nitrosylation and GSH-protein adducts (9,28), (ii) S-nitrosylation is chemically unstable and can react with GSH to become relatively more stable GSH adducts (9,10), and (iii) biotin switch assays are not very specific to distinguish these reversible modifications (29). In our study, HIF-1α stabilization was induced by GSSG-EE in C2C12 cells under conditions of minimal nitrosative stress, and its stabilization was regulated by Glrx, which specifically reverses GSH-protein adducts.…”
Section: Lack Of Glrx Improves Ischemic Hind Limb Revascularization Imentioning
confidence: 99%
“…S-nitrosylation and S-sulfenylation are chemically unstable and further react with GSH, which is the most abundant small intracellular thiol, to form GSH adducts (9,10). A cytosolic thioltransferase, glutaredoxin-1 (Glrx), specifically and efficiently catalyzes reduction of GSH-protein adducts (11); thus, Glrx-regulated GSH-protein adducts can affect redox signaling and play an important role in pathophysiological conditions (12).…”
mentioning
confidence: 99%
“…Similarly, recombinant Trx was used to reduce cellular proteins induced to the Snitrosated state by treatment with S-nitrosocysteine [46], which were then alkylated and identified by mass spectrometry -to supposedly identify targets of S-nitrosation. A potential caveat is that that S-nitrosocysteine also induces widespread protein disulfides [47], which Trx disulfide reductase is fully capable of reducing and so many disulfide-modified proteins are likely to have been misidentified as S-nitrosated. To be clear, we fully anticipate Trx to be capable of reducing Snitrosated proteins, as thiol-containing molecules will generically do this, but whether it does so directly in cells, or whether they first transition to a disulfide is difficult to establish (Figure 2).…”
Section: Mechanisms Of Protein Denitrosationmentioning
confidence: 99%
“…Finally, Wang et al used mass spectrometry to compare the relative stoichiometry of S-nitrosation and disulfides formation on several cysteines within glutathione-S-transferase Pi after exposure to Snitrosocysteine. S-nitrosation was accompanied by disulfide formation, but is was notable that disulfides formed at low concentrations of S-nitrosocysteine (5 µM), preceding measurable increases in S-nitrosation [47]. Only after excess S-nitrosocysteine (>400 µM) was utilised did the proportion of S-nitrosated protein surpass that of disulfide.…”
Section: Considerations On the Stoichiometry Of Protein S-nitrosationmentioning
confidence: 99%